(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This case study explores the intersection of sustainable sourcing practices and nutritional quality in hotel kitchens, emphasizing their combined impact on environmental sustainability and public health. The research investigates how hotels that adopt sustainable sourcing focusing on local, organic, and ethically produced ingredients can improve the nutritional quality of their offerings while meeting the increasing consumer demand for healthier, more transparent food choices. Through qualitative and quantitative analyses of various hotel kitchens, the study identifies key benefits of sustainable sourcing, including reduced carbon footprints, fresher and more nutrient-dense meals, and enhanced guest satisfaction. Additionally, it examines the challenges hotels face in implementing these practices, such as increased costs and supply chain complexities. The findings suggest that while the adoption of sustainable sourcing practices may involve initial financial and logistical hurdles, the long-term advantages, including stronger brand reputation and alignment with global sustainability goals, outweigh these challenges. The study also highlights the importance of training kitchen staff and fostering strong supplier relationships to ensure the consistent delivery of high-quality, sustainable meals. Overall, this research underscores the critical role of sustainable sourcing in enhancing both the nutritional quality of food served in hotels and the sustainability of the food system, making a compelling case for its broader adoption across the hospitality industry. This case study contributes to the growing body of literature advocating for sustainable practices in food service operations, providing actionable insights for hotel managers and policymakers aiming to promote a healthier, more sustainable future.